Tactics of emotional appeal, persuasive and creative language in the implementation of advertising strategies on the examples of Belarus, Egypt, and the United Kingdom - Mounir, Antonious Samir (Journal of the Belarusian State University. Philology, 2024)
The article deals with the significance of using emotional appeal, creative, and persuasive tactics in order to effectively implement advertising strategies used in three different countries with three different languages and cultures. It has been demonstrated that advertising employing persuasive tactics has the potential to positively sway consumers and increase product recall. Additionally, it is important to keep in mind that these tactics might be received differently in various cultures. It has been established that advertising employs persuasive tactics to change consumers’ attitudes and behaviours. The analysis showed that emotional appeals elicit consumers’ strong emotions, such as happiness or sadness. The author has discovered that using inventive language tactics in advertising is crucial to its effectiveness and memorability. It is crucial to understand that the target audience, the good or service being advertised, and the linguistic and cultural context may all have an impact on how effective these strategies are.